2005
DOI: 10.1002/mrm.20566
|View full text |Cite
|
Sign up to set email alerts
|

On the cause of spatial displacement of long T1 species in segmented inversion recovery prepared imaging

Abstract: Using inversion recovery steady-state free precession segmented k-space imaging for the detection of myocardial infarction, we noticed that some structures appeared in the wrong locations of the image. In this work, the spatial displacement is demonstrated and explained from both theoretical and experimental points of view. The effect is due to a change in phase from segment to segment of the detected magnetization from species with long T 1 's such as cysts, fluid collections, and cerebrospinal fluid. Dependi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 6 publications
(6 reference statements)
0
7
0
Order By: Relevance
“…Fluid regions such as pericardial effusion, cysts, or cerebral spinal fluid (CSF) with long T1 relaxation time may lead to ghosting in segmented protocols, and will appear bright on magnitude reconstructed images which might be confused with fat. The PSIR method is shown to correct the polarity of pericardial effusion (69, 70), and the use of cardiac surface coil arrays with adaptive coil combining has been shown to reduce CSF ghosting (71) which in some instances might be confused with focal enhancement. Single shot methods avoid the problem of ghosting.…”
Section: Imagingmentioning
confidence: 99%
“…Fluid regions such as pericardial effusion, cysts, or cerebral spinal fluid (CSF) with long T1 relaxation time may lead to ghosting in segmented protocols, and will appear bright on magnitude reconstructed images which might be confused with fat. The PSIR method is shown to correct the polarity of pericardial effusion (69, 70), and the use of cardiac surface coil arrays with adaptive coil combining has been shown to reduce CSF ghosting (71) which in some instances might be confused with focal enhancement. Single shot methods avoid the problem of ghosting.…”
Section: Imagingmentioning
confidence: 99%
“…Initially, it was reported that this artifact was caused by oscillations in the transient approach to steady state for regions with long T 1 relaxation times (6). It was later shown through computer simulations, phantom experiments, and human studies that this artifact is due to a change in phase from k-space segment to k-space segment of the detected magnetization from species with long T 1 relaxation times such as cysts, fluid collections, and cerebrospinal fluid (7). Depending on the number of k-space segments and view ordering, structures can be replicated throughout the image or displaced by half of the phase-encoding field of view.…”
Section: Theory and Technique Descriptionmentioning
confidence: 99%
“…If phase encoding is performed such that interleaving of kspace segments (odd and even k-space lines) is done prior to image reconstruction, species with long T 1 relaxation times will have an alternating phase in the raw data reconstruction matrix. This is equivalent to multiplication by À1 on alternating rows of the raw data matrix (7). This k-space data multiplication is commonly used in MR image reconstruction (often called fft_shift, swapping, or chopping) and is equivalent to shifting the reconstructed image by half of the field of view.…”
Section: Theory and Technique Descriptionmentioning
confidence: 99%
See 2 more Smart Citations